Sarcoids in Donkeys: Common Types and Available Treatment - Semieka, Mohamed A.; Ali, Magda M.; Al-lethie, A. A. (Journal of Advanced Veterinary Research, 2012)
Different forms of equine sarcoids were recorded in 100 donkeys admitted to the Veterinary Teaching Hospital- Assiut University and to Veterinary Units that belong to Assiut Governorate during the period from 2008-2010. In each animal, different data including: (types, size, multiplicity and anatomical location) were recorded., Histopathological examination, surgical and nonsurgical techniques for treatment of sarcoids were applied. Results of this study showed 123 sarcoid lesions classified into: Fibroblastic (87); nodular (21); verrucous (9); mixed (6). Treatment of sarcoid varied in results according to the seat and type of lesion. Injection of the sarcoid by live attenuated Bacille Calmette-Guérin (BCG) vaccine was the best treatment in case of preocular sarcoid lesions..